Adaptive Behavior in the ASEAN Economic Community between a Logistics Sector and Commercials Sector - Sinrungtam, Wasana (Ph.D. in Social Sciences Journal, 2018)
The purpose of this research. 1) To study average levels of access for information, Knowledge, Understand and Adaptation of Commercial personnel in ASEAN Economic Community 2) To study average levels of relativity for information, Knowledge, Understand and Adaptation of Commercial personnel in ASEAN Economic Community and 3) To test relationship of involvement, perception, cognition and adapting behavior between logistics companies and trades sector for ASEAN Economics Community (AEC). There were 400 samples. The samples were the staff in logistics companies and commercials sector in Bangkok and metropolitan. The findings show that most respondents were female between 20-30 years and living in metropolitan. Respondents were general staff. They worked in Thai companies and they earned less than 20,000 baht/ month. They received information about AEC from internet. Their level of involvement, perception, cognition and adapting for AEC of logistics companies were highest. The commercial sector had a relationship of involvement and perception cognition and adapting behavior in the medium level. It is concluded by the model equation that logistics companies and commercials sector with the AEC information related to involvement, the perception and cognitive of staff which lead to the adapting behavior of staff to be ready for the AEC.